2013
DOI: 10.1016/j.ajpath.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Rather than Quantitative Changes Are Hallmarks of Fibroblasts in Bleomycin-Induced Pulmonary Fibrosis

Abstract: Pulmonary fibrosis is characterized by accumulation of activated fibroblasts that produce excessive amounts of extracellular matrix components such as collagen type I. However, the dynamics and activation signatures of fibroblasts during fibrogenesis remain poorly understood, especially in vivo. We examined changes in lung tissue cell populations and in the phenotype of activated fibroblasts after acute injury in a model of bleomycin-induced pulmonary fibrosis. Despite clustering of collagen type I-producing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 51 publications
6
82
0
Order By: Relevance
“…Interestingly, a recent study has demonstrated that quite similar functions are affected in isolated activated fibroblasts in BLM-induced pulmonary fibrosis, suggesting that activated resident fibroblasts may migrate to damaged sites, differentiate into myofibroblasts, and generate fibrotic legions by secreting ECM components (Tsukui et al, 2013). Taking these results into consideration, the biofunctional changes detected on day 3 may reflect BLM-induced activation of resident fibroblasts in the lung, although no sign of fibrosis was observed in the histopathological analysis.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, a recent study has demonstrated that quite similar functions are affected in isolated activated fibroblasts in BLM-induced pulmonary fibrosis, suggesting that activated resident fibroblasts may migrate to damaged sites, differentiate into myofibroblasts, and generate fibrotic legions by secreting ECM components (Tsukui et al, 2013). Taking these results into consideration, the biofunctional changes detected on day 3 may reflect BLM-induced activation of resident fibroblasts in the lung, although no sign of fibrosis was observed in the histopathological analysis.…”
Section: Discussionmentioning
confidence: 85%
“…We sought to evaluate the contribution of FOXM1 to in vivo fibrogenesis by selectively deleting it from Col1-expressing cells. Under baseline conditions, Col1a2 expression in the lung is almost entirely limited to resident fibroblasts (57). It is well known that during fibrotic responses, other cells, including epithelial cells, can undergo mesenchymal transition (39,58), thus expressing Col1 and being subject to Cre-mediated deletion under the control of the Col1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate here a significant increase in expression of these markers after exposure to conditioned medium from MWCNT treated HBE cells. Increased levels of OPN, PC-1 and TIMP-1 are noted in rodent lungs in bleomycin induced pulmonary fibrosis [36-38]. TN-C is prototypic family member of Tenascin family of extracellular matrix glycoproteins.…”
Section: Discussionmentioning
confidence: 99%